Immunogenicity Risk Profile of Nanobodies - Ackaert, Chloé; Smiejkowska, Natalia; Xavier, Catarina; Sterckx, Yann G. J.; Denies, Sofie; Stijlemans, Benoit; Elkrim, Yvon; Devoogdt, Nick; Caveliers, Vicky; Lahoutte, Tony; Muyldermans, Serge; Breckpot, Karine; et al. (Frontiers in Immunology, 2021)
Nanobodies (Nbs), the variable domains of camelid heavy chain-only antibodies, are a promising class of therapeutics or in vivo imaging reagents entering the clinic. They possess unique characteristics, including a minimal size, providing fast pharmacokinetics, high-target specificity and an affinity in the (sub-)nanomolar range in conjunction with an easy selection and production, which allow them to outperform conventional antibodies for imaging and radiotherapeutic purposes. As for all protein theranostics, extended safety assessment and investigation of their possible immunogenicity in particular are required. In this study, we assessed the immunogenicity risk profile of two Nbs that are in phase II clinical trials: a first Nb against Human Epidermal growth factor Receptor 2 (HER2) for PET imaging of breast cancer and a second Nb with specificity to the Macrophage Mannose Receptor (MMR) for PET imaging of tumor-associated macrophages. For the anti-HER2 Nb, we show that only one out of 20 patients had a low amount of pre-existing anti-drug antibodies (ADAs), which only marginally increased three months after administering the Nb, and without negative effects of safety and pharmacokinetics. Further in vitro immunogenicity assessment assays showed that both non-humanized Nbs were taken up by human dendritic cells but exhibited no or only a marginal capacity to activate dendritic cells or to induce T cell proliferation. From our data, we conclude that monomeric Nbs present a low immunogenicity risk profile, which is encouraging for their future development towards potential clinical applications.